(3JaSjQ cJGH GdYdds - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3hHGSe QH GdYGdejf JYGdi hgPG UOQ eG GHJOGfG Hg Ke fWb HCf bGd CfJ GdYdje GdMcje GdbOjQ GdQMje s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3aEPG CUGH Pdc GdMQ XgQJ GdQWhHI hGdYdI ai Pdc dCf GdeGA hUd Edi GdJQGK cdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs